2009
DOI: 10.1292/jvms.71.1105
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Bacillary Hemoglobinuria in Japanese Black Cows

Abstract: ABSTRACT. Four pasture-fed Japanese Black cows showed the main clinical symptoms of severe hemoglobinuria at different periods between 2003 and 2007. Hematological analyses at the first consultation revealed severe anemia, and biochemical analyses indicated both severe hemolysis and disruption of hepatic function. Although the first 2 patients died, the hemoglobinuria and general condition of the remaining 2 cows, who were immediately initiated on large doses of antibiotics, improved within 3 days. Clostridium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
24
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 6 publications
1
24
1
1
Order By: Relevance
“…Although previous reports suggested that the clinical course of BHU is rapid and the outcome is almost invariably fatal [2,12], in both of the present cases as well as previous cases [9] subsequently diagnosed as BHU, the animals successfully recovered with the help of antibacterial therapy. For recovery from BHU, it is critical for the dose and route of antibiotic administration at the first treatment to achieve an effective blood concentration of the antibiotic against C. haemolyticum [1,5,6,9].…”
mentioning
confidence: 39%
See 4 more Smart Citations
“…Although previous reports suggested that the clinical course of BHU is rapid and the outcome is almost invariably fatal [2,12], in both of the present cases as well as previous cases [9] subsequently diagnosed as BHU, the animals successfully recovered with the help of antibacterial therapy. For recovery from BHU, it is critical for the dose and route of antibiotic administration at the first treatment to achieve an effective blood concentration of the antibiotic against C. haemolyticum [1,5,6,9].…”
mentioning
confidence: 39%
“…These practical limitations of sampling make it difficult to establish an accurate diagnosis for suspected cases of BHU once the animals have completely recovered after antibacterial therapy. Recently, Takagi et al [9] reported the first case of BHU in a Japanese Black cow, which recovered completely, and the diagnosis was confirmed by polymerase chain reaction (PCR) analysis using a whole blood sample collected before antibacterial therapy. However, to our knowledge, there is no documented report on the possibility or limitations of using molecular diagnosis to identify C. haemolyticum in blood samples collected from infected cattle either during or after antibiotic therapy.…”
mentioning
confidence: 99%
See 3 more Smart Citations